2016
DOI: 10.1039/c5cp07728a
|View full text |Cite
|
Sign up to set email alerts
|

Droplet coalescence and clustering behavior in microsphere-filled polymeric emulsions under shear flow: the key role of asymmetric interfacial affinities

Abstract: The flow-induced spatial organization of the droplet phase in ternary polymeric emulsions consisting of two Newtonian fluids, namely polyisobutylene (PIB) and polydimethylsiloxane (PDMS), in the presence of a small amount of solid polystyrene (PS) microspheres are explored by direct flow visualization. The results suggest that the asymmetric affinities of interfacially located PS microspheres to two fluid components lead to diverse flow-induced morphologies in PIB/PDMS blends with different compositions. In 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…Similar shear banding was not observed in the inverse PDMS/PIB (10/90) blends within all PS microsphere concentrations (0–4 wt %) investigated . In that case, the θ of PS microspheres is 57 ± 6°.…”
Section: Results and Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Similar shear banding was not observed in the inverse PDMS/PIB (10/90) blends within all PS microsphere concentrations (0–4 wt %) investigated . In that case, the θ of PS microspheres is 57 ± 6°.…”
Section: Results and Discussionsupporting
confidence: 71%
“…The addition of 0.1 wt % PS microspheres (Figure b) leads to the formation of grape-like PIB droplet clusters consisting of 3–10 small droplets ( R V = ∼52 μm) and distributed randomly within the PEO matrix, resembling the structure found by Thareja and Velankar . Our previous work with PDMS/PIB (10/90) blends filled with PS microspheres which were preferentially wetted by the PIB matrix phase displayed a similar phenomenon . It is suggested that this process will be facilitated greatly in the presence of the shear flow and by the wall confinement effect.…”
Section: Results and Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The PIB droplets in blend filled with PS microspheres appear dark but still acquire a near-spherical shape (Figure b). The droplet size is larger in microsphere-filled blend, which could be interpreted by particle-induced coalescence via the bridging-dewetting mechanism. , In contrast, the droplets in the emulsion containing ellipsoids have distinctly irregular shapes (Figure c). These morphological consequences are ascribed to the fact that particles can be trapped by the fluid interface at an adequately high coverage to jam the interface against coalescence at quiescence or small shear intensities. , Additionally, the bulk elasticity of droplet can also arrest coalescence to form irregular droplets .…”
mentioning
confidence: 98%
“…Mao et al [30,31] reported two studies of blends of polyisobutylene and polydimethylsiloxane in the presence of either spherical or ellipsoid polystyrene particles. They concluded that during shearing, droplets became elongated and rotated periodically about their major axes while aligning along the vorticity direction in ellipsoid-filled emulsions due to both an extremely small Reynolds number that arrested the coalescence and a strong confinement effect.…”
Section: Polymer-oil and Polymer-polymer Interfacesmentioning
confidence: 99%